EFEKTIVITAS DAN STRATEGI PENERIMAAN RETRIBUSI PARKIR DI TEPI JALAN UMUM (STUDI KASUS KOTA MALANG) - Lathifaniya, Palestin Tara; Susilo (Journal of Development Economic and Social Studies, 2023)
To realize local government programs and activities, Local Own Revenue (PAD) plays a very important role. Increasing Regional Original Income (PAD) absolutely must be carried out by regional governments as an effort to finance the needs of their own government households. Based on data reported by BPS, it was noted that in the last five years there has been an increase in the number of vehicles in Malang City. the high growth in the number of motorized vehicles can be assessed as a potential to boost the rate of growth in the realization of parking fees in Malang. However, when viewed from the target and realization table, it can be seen that in 2018-2019 revenue realization did not reach the expected target. The presence of a large number of illegal parking attendants in the city of Malang gives the impression that the system is still not working well. This is a major problem because levies by illegal parking attendants are not included in the Local Revenue (PAD) of Malang City. This analysis is carried out by calculating the level of effectiveness, SWOT analysis and IPA analysis. Where, in 2018 and 2019 it was categorized as effective and quite effective. The decline was caused by factors such as the lack of facilities and infrastructure, the absence of a shift in technology in the collection system and the behavior of parking attendants that was not in accordance with their duties and responsibilities.